2010
DOI: 10.1007/s11003-010-9266-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of wear resistance and nanostructure of tertiary Al2O3/Y2O3/CNT pulsed electrodeposited ni-based nanocomposite

Abstract: Electrodeposition of tertiary Alumina/Yitria/carbon nanotube (Al 2 O 3 /Y 2 O 3 /CNT) nanocomposite by using pulsed current has been studied. Coating process has been performed in nickel sulphate bath and nanostructure of the obtained compound layer was examined with high precision figure analysis of SEM nanographs. The effects of process variables, i.e. Y 2 O 3 concentration, treatment time, current density and temperature of electrolyte have been experimentally studied. Statistical methods were used to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…It has been revealed that by changing the size of nanoparticles, wear properties of coatings will change significantly. In the case of average size of nanoparticles ranking of effective factors by their relative contributions is the same as for wear rate which shows strong relation between these two measured properties of coatings [105]. This relation can be seen in Fig.…”
Section: Size Dependency In Nanocomposite Layerssupporting
confidence: 55%
See 1 more Smart Citation
“…It has been revealed that by changing the size of nanoparticles, wear properties of coatings will change significantly. In the case of average size of nanoparticles ranking of effective factors by their relative contributions is the same as for wear rate which shows strong relation between these two measured properties of coatings [105]. This relation can be seen in Fig.…”
Section: Size Dependency In Nanocomposite Layerssupporting
confidence: 55%
“…The Relation between average size of nanoparticles and wear rates for electrodeposited tertiary nanocomposite layer [105] effects of some process variables have been experimentally studied and statistical methods were used to achieve the minimum wear rate and average size of nanoparticles. It has been revealed that by changing the size of nanoparticles, wear properties of coatings will change significantly.…”
Section: Size Dependency In Nanocomposite Layersmentioning
confidence: 99%
“…For nickel matrix electrodeposits, a great variety of particles have been used such as oxides i.e. TiO 2 [41,42], Al 2 O 3 [43], CeO 2 [44,45], ZrO 2 [46], graphene oxide GO [47], carbon nanotubes CNT; Al 2 O 3 /Y 2 O 3 /CNT [48], carbides like SiC [49][50][51], WC [52] and nitrides such as TiN [53] and Si 3 N 4 [54].…”
Section: Electrodeposition Of Nickel Nanocompositesmentioning
confidence: 99%